2023
DOI: 10.1093/isd/ixad013
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary phylogenomic analyses reveal multiple reversions to nocturnal behavior and morphology within the primarily diurnal tribe Adesmiini (Coleoptera: Tenebrionidae)

Abstract: The darkling beetle tribe Adesmiini (Tenebrionidae: Pimeliinae) is a prominent part of African and western Palearctic desert faunas, with most species being day-active fast-running detritivores. Taxonomic diversity within the tribe is highest in the southern Afrotropical realm (where all genera are present); only 1 genus, the species-rich Adesmia, occurs north of the Sahara. Despite notable species, such as the fog-basking beetle Onymacris unguicularis (a focal taxon in desert ecological research), Adesmiini h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…S1 in Kamiński et al 2024). Furthermore, this study revealed a great degree of convergence between the molecular methodologies of Ragionieri et al (2023) and Swichtenberg et al (2023).…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…S1 in Kamiński et al 2024). Furthermore, this study revealed a great degree of convergence between the molecular methodologies of Ragionieri et al (2023) and Swichtenberg et al (2023).…”
Section: Resultsmentioning
confidence: 53%
“…Extracts were sent to Daicel Arbor Biosciences for library preparation and targeted enrichment using a MyBaits probe kit designed to capture 618 proteincoding genetic loci (see Kanda 2017 andSwichtenberg et al 2023). Libraries were sequenced on a NovaSeq 6000 system using 150 bp paired-end runs.…”
Section: Newly Sequenced Materialsmentioning
confidence: 99%
See 2 more Smart Citations